IMMUNOMODULATION EFFECT OF LEVAMISOLE AND IMMULITE ON UTERINE MICROBIAL PICTURE IN REPEAT BREEDING COWS
Forty (40) cyclic non breeding cows presented at lVCC were assigned to four equal (10) groups Levamisole s/c. three injections at weekly interval@ 2.5 mg/kg body weight (group I), lmmulite an herbal drug 20 ml orally for 1 0 days (group II), combination therapy of levamisole + immulite with same dose schedule (group Ill) was administered Ten animals subjected to saline uterine lavage (60 ml lukewarm normal saline) served as control (group IV